STRATEGI PENGEMBANGAN KAWASAN WISATA DANAU LINOUW DI KOTA TOMOHON PROVINSI SULAWESI UTARA - Darken Tabuni; Gene H. M. Kapantouw; Leonardo R. Rengkung (AGRI-SOSIOEKONOMI, 2015)
North Sulawesi in addition to having some of the leading tourist attractions such as Bunaken Marine Park also has the attraction of alternative that still needs to be developed attractions include Lake Linouw in Tomohon. The purpose of this study was to identify appropriate development strategies in the tourist area of Lake Linouw in Tomohon, North Sulawesi. Research method was descriptive methods. Determination of the sample is based on non-probability sampling techniques. Collecting data through pre-survey, survey questionnaires, and study the literature. Data analysis has used SWOT analysis. The results showed that the tourist area of Linouw Lake at Tomohon, North Sulawesi is the growth strategies of concentration through vertical integration or the strategy of Rapid Growth Strategy (strategy of rapid growth). Therefore, it can be concluded that the main strategy to develop the tourist area of Lake Linouw be competitive position is strong and has a high tourist pull. Based on these research results, it is suggested that relevant parties should maintain tourist area Linouw Lake at Tomohon in a competitive position in the strong growth to improve tourist pull high and considering the relatively expensive tourist prices.